Heat–Cool: A Simpler Differential Scanning Calorimetry Approach for Measuring the Specific Heat Capacity of Liquid Materials - Brandon C. Wada; Oliver W. M. Baldwin; Gerald R. Van Hecke (Thermo, 2023)
Specific heat capacity at constant pressure cp (J K−1 g−1) is an important thermodynamic property that helps material scientists better understand molecular structure and physical properties. Engineers control temperature (through heat transfer) in physical systems. Differential Scanning Calorimetry (DSC) is an analytical technique that has been used for over fifty years to measure heat capacities with milligram size samples. For existing procedures, such as ASTM E1269−11 (2018), the accuracy of molar heat capacity measurements is typically ±2–5% relative to the literature values, even after calibration for both heat flow and heat capacity. A comparison of different DSC technologies is beyond the scope of this paper, but the causes of these deviations are common to all DSC instruments, although the magnitude of the deviation (observed and accepted) varies with instrument design. This paper presents a new approach (Heat–Cool) for measuring more accurate and reproducible specific heat capacities of materials. In addition to better performance, the proposed method is faster and typically requires no additional calibration beyond the routine calibration of temperature and heat flow, with melting point standards common to all applications of DSC. Accuracy, as used throughout this paper, means deviation from the literature. The estimated standard deviation of repeated measurements of the cp values obtained with the Heat–Cool technique typically falls in the ±1–2% range.